PENGARUH MOTIVASI TERHADAP PRESTASI BELAJAR SAINS SISWA KELAS VII SMP NEGERI 2 JAWA MARAJA BAH JAMBI KABUPATEN SIMALUNGUN TAHUN PELAJARAN 2018/2019 - RISJUNARDI DAMANIK (JURNAL ILMIAH KOHESI, 2019)
This research was conducted with the aim to determine the effect of learning motivation on science learning achievement of Grade VII students of SMP Negeri 2 Jawa Maraja Bah Jambi, Simalungun Regency. This research was conducted in July to August 2019. The population is equal to the number of samples, 34 people (total sample). To find out the correlation between the influence of learning motivation on science learning achievement of Grade VII students of SMP Negeri 2 Jawa Maraja Bah Jambi, Simalungun Regency, calculated By using the Product Moment correlation test, the hypothesis was proved by a significant test in the student statistical correlation or a t test at a significant level of 0.05 and to find out the amount of contribution between the X and Y variables was calculated by the determination test. The average score of students' science learning achievement is 80.18 which is an average learning achievement that is quite high. The average questionnaire score of students' motivation to learn science is 73.53 which is a high average questionnaire. From the results of the correlation test, the correlation correlation between the effect of motivation on students' scientific learning achievement or r: 0.819 is obtained. Based on the qualification of the correlation coefficient, the correlation between the two variables above includes a correlation coefficient that is quite high. From the results of hypothesis testing, with the t test, obtained t count: 5.74 and at the real level α = 0.05 and dk = 32 obtained t-table: 1.70. So, the count is greater than the t-table, so in this case Ho is rejected and Ha is accepted, meaning that there is a real influence between learning motivation on science learning achievement of Grade VII students of SMP Negeri 2 Jawa Maraja Bah Jambi, Simalungun Regency, 2018/2019 Academic Year . Based on data analysis using the test of determination, that the contribution / influence between learning motivation on students' scientific learning achievement is 50.41%. This means that 67.07% of scientific learning achievement achieved by students in class influence of motivation on student achievement in science learning is influenced by motivation in learning.